Assessing the need for traffic signalization from the perspective of local government units - Amistad, Franklyn T. (2006)
It is a fact that some cities in the Philippines are confronted with traffic problems brought about by the uncontrollable growth of population and the transportation system. And despite all the engineering efforts of the local government units to address the traffic problems of the different cities of Metro Manila, traffic problems such as road accidents, congestion, pollution, and energy problems still confront them. This study focuses on assessing the need for traffic signalization from the perspective of local government units (LGUs). The information revealed in this study is based on the perspective of the 23 LGUs or 23% of the 98 LGUs outside Metro Manila through key informant interviews.
Most of the city respondents are thickly populated. Majority of them are first class cities wherein there is a continuous increase in the number of registered motor vehicles every year. The level of necessity and level of attainment of objective for traffic signalization are very high and high, respectively. Some of the LGUs have not installed traffic signals because of budget constraint. They tapped the expertise of Traffic Engineering Center (TEC), traffic Engineering and Management (TEAM), and the academe (e.g National Center for Transportation Studies) for the conduct of traffic engineering studies. TEC warrant is the most frequently used criteria considering vehicular volume as the indicator for warrants. Correlative analysis is used for this study. The F-ratio in the analysis of variance (ANOVA) at 0.05 level of significance is 12.21 which suggests that there is a significant difference in the level of attainment of objectives for traffic signalization among and between the cities. There is significant relationship between the basis in warrant in signalization for intersection and the level of necessity with chi-square (X^2 =12.547) and level of attainment of objective (X^2 = 7.35); between funding agencies and level of necessity (X2 = 6.84) and level of attainment of objective (X^2 = 7.78); and reason for non-implementation if traffic signalization and necessity (x^2 = 5.23) and level of attainment of objective (X^2 = 8.925). Also there is a significant relationship between the consultation which was administered by local officials and the level of attainment of objective for signalization. A traffic signalization process was formulated by the researcher and he recommends policy formulation of the guidelines in the implementation of traffic signalization among the local government units and agencies concerned.
Thesis (M.S. Transportation Engineering)--University of the Philippines Diliman.
Keywords: Traffic signs and signals -- Philippines; Local government -- Philippines